2013
DOI: 10.1002/ejic.201300279
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Glutathione Peroxidase‐Like Activity of a Cyclic Seleninate by DFT and Solvent‐Assisted Proton Exchange

Abstract: The mechanism of redox scavenging of a highly active cyclic seleninate was modeled by using density functional theory and solvent‐assisted proton exchange (SAPE), a method of microsolvation intended to mimic the role of the solvent in proton‐transfer reactions. Models of the proposed mechanism suggest that a pathway to a selenenyl sulfide, a possible dead‐end intermediate, is favored over regeneration of the seleninate catalyst. Alternate pathways through selenurane intermediates and a cyclic selenenate also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Similard eactivation through selenenyl sulfide formation has also been notedw ith numerous other cyclic seleninates in subsequent studies. Recent computational investigations of this process by Bayse and Ortwine [24] were generally consistent with the mechanism indicated in Scheme 3. Their computations used methanethiol as the overall reductant and incorporated solvation effects of water.…”
Section: Cyclic Seleninate Esterssupporting
confidence: 71%
“…Similard eactivation through selenenyl sulfide formation has also been notedw ith numerous other cyclic seleninates in subsequent studies. Recent computational investigations of this process by Bayse and Ortwine [24] were generally consistent with the mechanism indicated in Scheme 3. Their computations used methanethiol as the overall reductant and incorporated solvation effects of water.…”
Section: Cyclic Seleninate Esterssupporting
confidence: 71%
“…The selenenyl sulfide pathway is energetically preferred as expected from experimental results, but the reduction to the selenol is a key bottleneck and SAPE calculations predict a significant barrier (32 kcal/mol) (29). However, in our SAPE modeling of possible mechanisms for redox cycling for ebselen (Scheme 5) and, more recently, a cyclic seleninate (84), all low barrier pathways appear to converge on the selenenyl sulfide as an intermediate. To bypass this problem, we have proposed that ebselen and other GPx mimics avoid the bottleneck of selenol regeneration by oxidizing the selenenyl sulfide to the seleninyl sulfide (Scheme 6).…”
Section: Ebselenmentioning
confidence: 53%
“…Two classes of compounds that were first investigated as potential GPx mimetics by our group include the aliphatic and aromatic cyclic seleninate esters 1 12 and 2, 12c,13 as well as the corresponding spirodioxyselenuranes 3 14 and 4. 12c,13a Later studies of these types of compounds by Singh et al 15 and by Bayse and Ortwine 16 have also been reported. Certain members of both classes of compounds display >10-fold greater catalytic activity than that of ebselen.…”
Section: R a F Tmentioning
confidence: 92%